Brief aan mijn rechter - Simenon, Georges, 1903-1989; Kool, Halbo C. (Kool, Halbo Christiaan), 1907-1968 (Leeuwarden : Bruna, 1981)
De auteur van de brief bekent aan de rechter ... een moord uit liefde.
Lettre à mon juge